REDESAIN PONDOK PESANTREN DARUL HIJRAH PUTRI MARTAPURA - Dina, Umi Halisah; Anhar, Pakhri (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
Darul Hijrah Islamic Boarding School for females is a women's Islamic education institution in Martapura South Kalimantan and has been established since 1995. With a long time of more than 20 years, this boarding school has experienced many developments, especially in terms of development, but the development of Islamic boarding schools in the future will be increasingly complex considering the existence of government business programs that want to cooperate with the world of Islamic Boarding Schools in terms of the creative economy, this is intended to develop the economy and Human Resources (HR) within the boarding school environment. So from that the development of the creative economy as a learning media needs to be included to maintain the existence of this boarding school in the future. The method that was used in this report is a programming method which has two main steps: a) Programming which is a problem-tracking and; b) Schematic Design; a problem solving. The results of the method used finally got the Islamic creative educative place concept which is a combination of the two main variables namely Islamic education and creative education